Quantum Chemical Determination of Molecular Dye Candidates for Non-Invasive Bioimaging - Remy R. Cron; Jordan South; Ryan C. Fortenberry (Molecules)
Molecular dyes containing carbazole-based <semantics>π</semantics> bridges and/or julolidine-based donors should be promising molecules for intense SWIR emission with potential application to molecular bioimaging. This study stochastically analyzes the combinations of more than 250 organic dyes constructed within the D-<semantics>π</semantics>-D (or equivalently D-B-D) motif. These dyes are built from 22 donors (D) and 14 <semantics>π</semantics> bridges (B) and are computationally examined using density functional theory (DFT). The DFT computations provide optimized geometries from which the excited state transition wavelengths and associated oscillator strengths and orbital overlaps are computed. While absorption is used as a stand-in for emission, the longer the absorption wavelength, the longer the emission should be as well for molecules of this type. Nearly 100 novel dyes reported in this work have electronic absorptions at or beyond 1200 nm, opening the possibility for future synthesis and experimental characterization of new molecular dyes with promising properties for bioimaging.